New protein farnesyltransferase inhibitors in the 3-arylthiophene 2-carboxylic acid series: diversification of the aryl moiety by solid-phase synthesis. (February 2013) - Lethu, Sébastien; Bosc, Damien; Mouray, Elisabeth; Grellier, Philippe; Dubois, Joëlle
<x xml:space="preserve">Abstract</x> A new synthetic pathway was devised to reach tetrasubstituted 3-arylthiophene 2-carboxylic acids in a three-step solid-phase synthesis. This very efficient methodology provided more than 20 new compounds that were evaluated for their ability to inhibit protein farnesyltransferase from different species as well as Trypanosoma brucei and Plasmodium falciparum proliferation.